Developing Futsal as Extracurricular Achievement in Senior High School (The Analysis of Futsal Extracurricular in Senior High School of Bengkulu City) - Andes Permadi; Andika Prabowo; Septian Raibowo; Oddie Barnanda Rizky; Ari Sutisyana; Jerome Angelitud Porto (Kinestetik : Jurnal Ilmiah Pendidikan Jasmani, 2023)
This research aims to study, explain or interpret as well as knowing the development of futsal extracurricular achievements at Bengkulu City Public High School. In this study, researchers and informants' perspectives are adjusted using a qualitative descriptive approach. The eleven Bengkulu City State Senior High Schools served as the study's subjects. The instruments utilized are observation, surveys, and documentation. Out of 11 schools, Bengkulu City 1 Public High School and Bengkulu City 2 Public High School were the only two that could be declared to meet the standards for futsal extracurricular achievement development based on the obtained data. The futsal extracurricular achievement development at the Bengkulu City High School level was categorized as still not good with a percentage of 54.54%. Bengkulu City 3 State Senior High School, Bengkulu City 6 State Senior High School, and Bengkulu City 7 State Senior High School are the three schools in Bengkulu. The recommendation from the research is that schools should pay more attention to and provide support for futsal extracurricular activities. efforts that can be made are providing a proper field, providing adequate infrastructure, providing competent human resources, and providing sufficient budget funds for extracurricular futsal in their respective schools.